Penerapan Metode Principle Component Analysis (PCA) untuk Clustering Data Kunjungan Wisatawan Mancanegara ke Indonesia - Elly Muningsih; Noor Hasan; Gunawan Budi Sulistyo (LPPM Universitas Bina Sarana Informatika, 2020)
The tourism sector is one of the country's biggest foreign exchange earners. Foreign tourist visits to Indonesia reached 16.1 million during 2019. Therefore foreign tourist visits become a very important thing. In this study clustering will be carried out or grouping data on foreign tourist visits into 5 groups for the category of countries with very high, high, high enough, low and very low visits. Data processing was performed using the K-Means clustering method and the Principle Component Analysis (PCA) dimension reduction method. From the data processing, K-Means modeling results combined with the PCA method resulted in a smaller or better Davies Bouldin Index (DBI) evaluation value of 0.310 compared to K-Means modeling alone which obtained a DBI value of 0.382. The tools used in data processing are RapidMiner. The results of clustering are expected to be a reference for related parties to maximize the promotion of overseas tourism.